Beijing Pinggu Childhood Eye Study: The Baseline Refractive Characteristics in 6- to 12-Year-Old Chinese Primary School Students - Li, Yan; Xing, Yi; Jia, Chunlin; Ma, Jiahui; Li, Xuewei; Zhou, Jingwei; Zhao, Chenxu; Zhang, Haijun; Wang, Lu; Wang, Weihong; Qu, Jia; Zhao, Mingwei; et al. (Frontiers in Public Health, 2022)
Purpose To report the design and baseline data of a 3-year cohort study in Beijing Pinggu District primary school students in China after COVID-19. Methods Noncycloplegic and cycloplegic spherical equivalent refraction (SER) were measured, ocular biometry, including the axial length (AL), anterior chamber depth (ACD) and corneal power (CP), were collected before cycloplegia. Corneal radius (CR), AL-to-CR ratio, and lens power (LP) were calculated. Results Among the 4,806 (89.1%) eligible students (51.5% male), the prevalence of emmetropia, myopia, mild hyperopia, and mild-to-high hyperopia was 12.8, 30.8, 53.0, and 3.3% after cycloplegia, respectively. Myopia increased from 2.5% in 6- to 71.6% in 12-year-old students, with 9- and 10-year-olds showing the most prominent increases. The median of cycloplegic SER was 0.50 (IQR = 1.63), and the noncycloplegic SER was −0.38 D (IQR = 1.50), which is more negative than the cycloplegic refraction. The mean AL increased with age, from 22.46 ± 0.70 mm to 24.26 ± 1.07 mm. The ACD increased from 3.38 ± 0.28 mm to 3.70 ± 0.30 mm, and the AL-to-CR ratio increased from 2.91 ± 0.08 to 3.12 ± 0.13 between 6- and 12-year-old students. AL, CR and LP explained the SER variance with R2 of 86.4% after adjusting the age and gender. Conclusions and Relevance The myopia prevalence since emergence of COVID-19 rapidly increased from 6- to 12-year primary school Chinese children, especially after 7 years of age. The non-cycloplegia SER overestimated the prevalence of myopia, and the cycloplegic SER is a more accurate and reliable method to assess the prevalence of refractive status.